Experimental challenges in determining the rheological properties of bacterial biofilms. Issue 6 (14th October 2022) - Geisel, Steffen; Secchi, Eleonora; Vermant, Jan
Abstract : Bacterial biofilms are communities living in a matrix consisting of self-produced, hydrated extracellular polymeric substances. Most microorganisms adopt the biofilm lifestyle since it protects by conferring resistance to antibiotics and physico-chemical stress factors. Consequently, mechanical removal is often necessary but rendered difficult by the biofilm's complex, viscoelastic response, and adhesive properties. Overall, the mechanical behaviour of biofilms also plays a role in the spreading, dispersal and subsequent colonization of new surfaces. Therefore, the characterization of the mechanical properties of biofilms plays a crucial role in controlling and combating biofilms in industrial and medical environments. We performed in situ shear rheological measurements of Bacillus subtilis biofilms grown between the plates of a rotational rheometer under well-controlled conditions relevant to many biofilm habitats. We investigated how the mechanical history preceding rheological measurements influenced biofilm mechanics and compared these results to the techniques commonly used in the literature. We also compare our results to measurements using interfacial rheology on bacterial pellicles formed at the air–water interface. This work aims to help understand how different growth and measurement conditions contribute to the large variability of mechanical properties reported in the literature and provide a new tool for the rigorous characterization of matrix components and biofilms.